0292 Objective Short Sleep Duration is Associated with Increased 24-Hour Ambulatory Blood Pressure - Abdalla, Marwah; Cornelius, Talea; Chang, Bernard P; Schwartz, Joseph E; Shechter, Ari (Sleep (New York, N.Y.), 2019)
Introduction Short sleep duration is a contributor to cardiovascular disease (CVD) events and mortality. In particular, short sleep duration has been linked to an increased risk of high clinic blood pressure (BP). BP measured outside the clinic using 24-h ambulatory blood pressure monitoring (ABPM) is a better predictor of an individual’s CVD risk. We therefore aimed to examine the association between objectively-assessed sleep duration and 24-h ambulatory blood pressure (ABP). Methods The Masked Hypertension Study is a multi-site study of the prevalence and predictors of masked hypertension (i.e. ambulatory hypertension despite non-elevated clinic BP), comprising working adults from the New York area. Participants were excluded if they were taking antihypertensive drugs or had a screening BP >160/105 mmHg. Participants were fitted with a 24-h ABPM device (Model 90207; Spacelabs), and measures were taken at 28-30 min intervals. Objective sleep duration, and times of wakefulness and sleep during the 24-h ABPM period were derived from wrist-worn actigraphy (ActiWatch; Phillips Respironics), supplemented by diary reports. Linear regression, adjusted for age, sex, race/ethnicity, body mass index, smoking status, and diabetes were conducted on the relationship between sleep duration and the ABP measures. Results Participants (N=744, 59.5% female) were (mean ± SD) 45.2 ± 10.3 years old. Mean actigraphy-derived sleep duration was 6.8 ± 1.2 hours. Hours of sleep (continuous variable) was not associated with mean awake or asleep systolic BP (p=0.79 and p=0.75) or mean awake or asleep diastolic BP (p=0.23 and p=0.74). However, shorter sleep duration predicted higher mean 24-h systolic BP, B=-0.73, p=0.01, as well as higher mean 24-h diastolic BP, B=-0.83, p<0.001. Findings were consistent when sleep duration was dichotomized as short (<6 h) or not short (≥6 h). Conclusion Actigraphy-derived sleep duration was related to mean 24-h systolic and diastolic BP. To our knowledge, this is the largest study conducted which assessed sleep duration objectively while measuring 24-h ABP. These findings indicate that shorter sleep duration is associated with higher 24-h BP and potentially cardiovascular risk. Support (If Any) P01 HL047540